Analisis Hukum Perikatan Islam Terhadap Kerjasama Periklanan Google Adsense Pada Youtube - Muhammad Achid Nurseha; Muhammad Fajrul Hakim (Fakultas Ekonomi dan Bisnis Islam IAINU Kebumen, 2021)
The purpose of this study is to find out how the mechanism of Google Adsense advertising cooperation on Youtube and whether the mechanism is in accordance with Islamic law of engagement. This research is Library Research with a qualitative approach. The data collecting techniques are using the study of literatures, documents, Google's official website while to strengthen the data used interviews with Content Creators. The results of this study indicates that the Google Adsense advertising cooperation mechanism involves three parties, namely the Advertiser as the first party, Google as the second party and Content Creator as the third party. Advertisers ask Google for services to advertise their products and Google cooperates with Content Creators to serve ads. Advertiser pays to Google according to the agreement and Google will share the results with the Content Creator according to applicable regulations. The contract used from the perspective of Islamic law is called an ijarah agreement between the Advertiser and Google and a syirkah contract between Google and the Content Creator. In the course of the transaction or cooperation, it reflects the value of Islamic engagement law, both from contracts, transactions and reflects the value of principles in Islamic engagement law.